2024
DOI: 10.1200/jco.23.01390
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Health in Adolescents and Young Adults With Cancer

Brooke O. Cherven,
Jenna Demedis,
Natasha N. Frederick

Abstract: Sexual health (SH), an integral aspect of overall health and quality of life, can be negatively affected by cancer and cancer treatment. SH is influenced by biological, psychological, social, and cultural factors, and, for adolescents and young adults (AYAs), developmental factors. The AYA population (age 15-39 years) is diverse in terms of psychosexual development, interpersonal relationships, and varying levels of independence, resulting in unique SH needs for this population. AYAs with cancer are particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Sexuality and intimacy are important aspects of AYA health care and sexual health should be discussed early in the treatment process. 35 , 78 The results of this study demonstrated that AYA breast cancer survivors experience significantly more sexual QoL challenges compared to (female) AYA survivors of other cancer types. While discussing that sexual health is important for all AYA cancer survivors, those facing challenges related to sexuality, particularly breast cancer patients, might benefit from specialized interventions such as consultations with a sexologist.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Sexuality and intimacy are important aspects of AYA health care and sexual health should be discussed early in the treatment process. 35 , 78 The results of this study demonstrated that AYA breast cancer survivors experience significantly more sexual QoL challenges compared to (female) AYA survivors of other cancer types. While discussing that sexual health is important for all AYA cancer survivors, those facing challenges related to sexuality, particularly breast cancer patients, might benefit from specialized interventions such as consultations with a sexologist.…”
Section: Discussionmentioning
confidence: 66%
“…Although sexual health plays an important role in HRQoL of AYA cancer survivors, it is often inadequately addressed by health care professionals. 16 , 27 , 34 , 35 , 36 Furthermore, it is known from previously published literature that AYA cancer survivors experience ongoing problems with sexual functioning up to 2 years after their initial diagnosis. 37 Unfortunately, there is limited knowledge regarding long-term (>5 years after diagnosis) sexual health of AYA cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…There can be derailment in this development and health trajectories with the occurrence of a cancer diagnosis [ 3 ]. Although a cancer diagnosis inherently disrupts life for patients of all ages, cancer has an augmented impact on AYA patients, especially regarding fertility preservation, diagnosis and treatment of mental health concerns, a pause in education or career life goals, sexual health, and premature death [ 4 , 5 , 6 ]. In Canada, the current landscape of AYA care includes the delivery of oncology support at adult cancer centers, most of whom have limited resources or programming dedicated to the unique needs of this population [ 7 ].…”
Section: Introductionmentioning
confidence: 99%